1999
DOI: 10.1128/aem.65.5.2163-2169.1999
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of Two Recombinant Bacteria That Grow on ortho - and para -Substituted Chlorobiphenyls

Abstract: Cloning and expression of the aromatic ring dehalogenation genes in biphenyl-growing, polychlorinated biphenyl (PCB)-cometabolizing Comamonas testosteroni VP44 resulted in recombinant pathways allowing growth on ortho-and para-chlorobiphenyls (CBs) as a sole carbon source. The recombinant variants were constructed by transformation of strain VP44 with plasmids carrying specific genes for dehalogenation of chlorobenzoates (CBAs). Plasmid pE43 carries the Pseudomonas aeruginosa 142 ohb genes coding for the termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(25 citation statements)
references
References 52 publications
(65 reference statements)
1
18
0
6
Order By: Relevance
“…If the initial step involved oxygenation of the non-chlorinated ring and if this was the rate limiting step, rapid degradation of the 4-CBA product might explain our lack of 4-CBA detection during 4-CB degradation. Hrywna et al, for example, observed only ephemeral production of 4-CBA during complete degradation of 4-CB by a recombinant strain [8].…”
Section: Discussionmentioning
confidence: 99%
“…If the initial step involved oxygenation of the non-chlorinated ring and if this was the rate limiting step, rapid degradation of the 4-CBA product might explain our lack of 4-CBA detection during 4-CB degradation. Hrywna et al, for example, observed only ephemeral production of 4-CBA during complete degradation of 4-CB by a recombinant strain [8].…”
Section: Discussionmentioning
confidence: 99%
“…A sampling of the recent literature provides examples of the range of current approaches to biodegradation. Researchers have identified strains of bacteria that have the ability to break down or alter environmental pollutants such as petroleum products, polychlorinated biphenyls (PCBs) (Wagner-Do È bler et al, 1998;Hrywna et al, 1999), other halogenated aromatics (Sharak Genthner et al, 1997;Zeyer et al, 1985), toluene (Hubert et al, 1999) and nitrogen-containing heterocyclic aromatic analogues of polycyclic aromatic hydrocarbons (Pfaller et al, 1999). Organisms capable of such activity are often isolated by a screening process in which the target substance is provided as the carbon source or electron acceptor for the growth of a generalized inoculum (Hegeman, 1985;Maymo  -Gatell et al, 1997;Van Agteren et al, 1998).…”
Section: Current Methods Of Biodegradationmentioning
confidence: 99%
“…Because many of the genes coding for catabolic enzymes can be found on transposons or plasmids, Peters et al (1997) were able to track the horizontal in situ transfer of a plasmid-borne operon coding for phenol metabolism. By introducing specific dehalogenation genes into a bacterial strain capable of co-metabolizing PCBs, Hrywna et al (1999) demonstrated an improvement in the ability of the recipient strain to grow upon and metabolize much higher concentrations of substrate. Novel developments along these lines include the modification of degrading bacteria to fluoresce when actively breaking down a target substance, providing an in situ indicator of degradative progress (Ripp et al, 2000).…”
Section: Current Methods Of Biodegradationmentioning
confidence: 99%
“…The optimum concentration of 2-CBA for growth was around 2.5 to 3.0 mM for parental strain 142 (61), compared to 1.5 mM for recombinant PB2440(pE43); this could arguably be due to cognate ferredoxin or reductase components in the parent. However, in later experiments we have expressed the ohb genes in biphenyl-degrading C. testosteroni VP44, and the resulting recombinant, VP44(pE43), readily mineralized 10 mM each 2CBA and 2-chlorobiphenyl (36).…”
Section: Discussionmentioning
confidence: 99%